Genocide and resistance Nr. 13(1) - Streikus, Arūnas; Bubnys, Arūnas; Anušauskas, Arvydas; Jakubčionis, Algirdas; Jegelevičius, Sigitas; Brandišauskas, Valentinas; Žiūkas, Mindaugas; Labanauskas, Ramūnas; Zizas, Rimantas (Genocidas ir rezistencija, 2003)
Full Issue (paper copy scan)